CMOS-based active pixel for low-light-level detection: Analysis and measurements - Faramarzpour, Naser; Deen, M. Jamal; Shirani, Shahram; Fang, Qiyin; Liu, Louis W.C.; Campos, Fernando de Souza; Swart, Jacobus W. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
An analysis of the active pixel sensor (APS), considering the doping profiles of the photodiode in an APS fabricated in a 0.18 μm standard CMOS technology, is presented. A simple and accurate model for the junction capacitance of the photodiode is proposed. An analytic expression for the output voltage of the APS obtained with this capacitance model is in good agreement with measurements and is more accurate than the models used previously. A different mode of operation for the APS based on the dc level of the output is suggested. This new mode has better low-light-level sensitivity than the conventional APS operating mode, and it has a slower temporal response to the change of the incident light power. At 1μW/cm2 and lower levels of light, the measured signal-to-noise ratio (SNR) of this new mode is more than 10 dB higher than the SNR of previously reported APS circuits. Also, with an output SNR of about 10 dB, the proposed dc level is capable of detecting light powers as low as 20 nW/cm2, which is about 30 times lower than the light power detected in recent reports by other groups. © 2007 IEEE.
Keywords: Active pixel sensor (APS); Capacitance-voltage (C-V ) profile; CMOS photodetector; High-sensitivity photodetector; Low-level light detection; Silicon photodetector; Capacitance; CMOS integrated circuits; Photodetectors; Photodiodes; Semiconductor device models; Sensitivity analysis; Capacitance-votage (C-V) profile; Pixels